The institutional framework of the 2012 elections in Ghana: consolidating or reversing democratic achievement? (2013)
The 2012 elections were peaceful, but the results were contested by the New Patriotic Party in a petition brought to the Supreme Court challenging the National Democratic Congress and the Electoral Commission of Ghana. Revelations during the hearing of the petition raised some disquiet about the abilities of the ECG and the integrity of Ghana’s electoral institutions. The fallout from the 2012 elections demands a critical intellectual engagement with the institutional foundation of the elections. There were several institutional changes in the Ghanaian system in the build-up to the elections as well as changes in the general political economy of the country that have made access to public office particularly attractive. This article reviews the institutional context of the elections and examines the constitutional and non-constitutional rules relating to electoral governance, focusing on such issues as electoral management, delimitation of constituencies and assembly size, electoral formula, voting procedure and ballot structure and the party system. It demonstrates how these institutions were implicated in the challenges relating to the electoral process during the 2012 elections, providing insights into how to overcome them.